2018
DOI: 10.1111/nep.13409
|View full text |Cite
|
Sign up to set email alerts
|

Differential response to renal replacement therapy in neonatal‐onset inborn errors of metabolism

Abstract: Severe urea cycle defects (UCD), organic acidemias (OA) and maple syrup urine disease (MSUD) are life-threatening disorders presenting in the first days of life. Renal replacement therapy (RRT) is an emergency option in affected newborns, mostly performed as ultima ratio. We report our 10-year experience using emergency RRT in newborns with UCD, OA and MSUD. Twelve newborns (eight with UCD, two with methylmalonic acidemia and two with MSUD) underwent emergency RRT. The overall survival rate to RRT was 58.3%. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…Due to limitations in access to diagnostic equipment and laboratories in local hospitals, pre‐diagnoses of IMDs may occur late. Diagnostic tests and treatments should be carried out at the same time 16 . Such disorders usually require urgent detoxification treatment, and our hospital serves as a reference center given the availability of hemodialysis and advanced treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Due to limitations in access to diagnostic equipment and laboratories in local hospitals, pre‐diagnoses of IMDs may occur late. Diagnostic tests and treatments should be carried out at the same time 16 . Such disorders usually require urgent detoxification treatment, and our hospital serves as a reference center given the availability of hemodialysis and advanced treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the elimination of toxic metabolites to avoid neurological complications should be considered a medical emergency. CKRT is an effective treatment for acute crises in some IEM [ 13 , 14 ]. In the present study, CKRT was shown to quickly reduce toxic metabolites (ammonia, leucine) in patients diagnosed with IEM.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal-onset UCDs or OAs are life-threatening disorders leading to hyperammonemic coma and requiring early specific emergency treatments [17,18]. Patients surviving the neonatal period experience recurrent metabolic decompensations later in life (generally triggered by undercurrent catabolic stressors) and poor prognosis in spite of appropriate long-term conventional management [1].…”
Section: Discussionmentioning
confidence: 99%